2023
DOI: 10.1002/psc.3482
|View full text |Cite
|
Sign up to set email alerts
|

Development of membrane‐active peptide therapeutics in oncology

Abstract: Membrane-active peptides play an essential role in many living organisms and their immune systems and counter many infectious diseases. Many have dual or multiple mechanisms and can synergize with other molecules, like peptides, proteins, and small molecules. Although membrane-active peptides have been intensively studied in the past decades and more than 3500 sequences have been identified, only a few received approvals from the US Food and Drug Administration. In this review, we investigated all the peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Each peptide is associated with an extended hydrophobic domain, comprising multiple Leu and Val residues on one face of the helix, that enables binding to (phospho)lipids in the bacterial cell membrane and a hydrophilic domain on the opposite face, containing multiple Lys residues, that promotes loss of integrity of the membrane [27]. The ability of figainin 2BN to produce death of non-small cell lung adenocarcinoma A549 cells, breast adenocarcinoma MDA-MB-231 cells and colorectal adenocarcinoma HT-29 cells during a 24 h incubation at relatively low concentrations (LC50 values in the range 7 to 14 µM) suggests that the peptide may represent a template for the design of anti-cancer drugs, particularly when the tumor is not responsive to conventional pharmaceutical agents [28]. Previous studies from the laboratory have shown that loss of cell viability produced by cytotoxic frog skin peptides under the conditions of the present study is rapid [29], suggesting that the mechanism of action involves non-specific destruction of the integrity of the plasma membrane rather than induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each peptide is associated with an extended hydrophobic domain, comprising multiple Leu and Val residues on one face of the helix, that enables binding to (phospho)lipids in the bacterial cell membrane and a hydrophilic domain on the opposite face, containing multiple Lys residues, that promotes loss of integrity of the membrane [27]. The ability of figainin 2BN to produce death of non-small cell lung adenocarcinoma A549 cells, breast adenocarcinoma MDA-MB-231 cells and colorectal adenocarcinoma HT-29 cells during a 24 h incubation at relatively low concentrations (LC50 values in the range 7 to 14 µM) suggests that the peptide may represent a template for the design of anti-cancer drugs, particularly when the tumor is not responsive to conventional pharmaceutical agents [28]. Previous studies from the laboratory have shown that loss of cell viability produced by cytotoxic frog skin peptides under the conditions of the present study is rapid [29], suggesting that the mechanism of action involves non-specific destruction of the integrity of the plasma membrane rather than induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%